Representations of Power at Police Headquarters: A Discourse Analysis of Mapolres Architecture in Geospatial Reports - Bakharuddin Muhammad Syah; Rendy Ananta Prasetya (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
This study examines how the physical spatial arrangement of Police Resort Headquarters (Mapolres) in Indonesia represents and reproduces power relations, internal hierarchy, unit segregation, and the institution’s relationship with the surrounding community. Using a qualitative approach with architectural discourse analysis and geospatial netnography, this research utilizes online data such as Google Street View images, user‑uploaded photos on Google Maps, YouTube virtual tour videos, and photos from online news portals. A purposive sample of 10 Mapolres was selected from rural (4 locations), semi‑urban (3 locations), and urban (3 locations) areas on the islands of Java and Sumatra. The analysis is guided by the frameworks of the sociology of space (Lefebvre, 1991), architecture of power (Foucault, 1977), and dramaturgy (Goffman, 1959). The results show three main findings. First, internal hierarchy is represented through the centralized and protected location of leadership offices (upper floors or end of corridors), ceremonial yards that place leaders in a central position, and rank‑based access zoning. Second, functional unit segregation is reflected in the closed and hidden Criminal Investigation Unit (Reskrim) room (back stage), the open and publicly accessible Traffic Unit (Lantas) room (front stage), and the Logistics room located in the unseen rear area. Third, the relationship with the surrounding community is represented through fences, security posts, and waiting rooms: urban Mapolres tend to have high walls with separate waiting rooms, creating social distance and potential distrust; conversely, rural Mapolres are more open and accessible. This study concludes that Mapolres architecture is not a neutral space but a spatial text that conveys messages of power, control, and social distance. Recommendations include evaluating Mapolres designs to be more open and public‑friendly, as well as conducting further studies with physical observation and interviews.